Calmer: a robot for managing acute pain effectively in preterm infants in the neonatal intensive care unit. (March 2019) - Holsti, Liisa; MacLean, Karon; Oberlander, Timothy; Synnes, Anne; Brant, Rollin
Abstract: Introduction: For preterm infants in the neonatal intensive care unit, early exposure to repeated procedural pain is associated with negative effects on the brain. Skin-to-skin contact with parents has pain-mitigating properties, but parents may not always be available during procedures. Calmer, a robotic device that simulates key pain-reducing components of skin-to-skin contact, including heart beat sounds, breathing motion, and touch, was developed to augment clinical pain management. Objective: Our objective was to evaluate the initial efficacy of Calmer for mitigating pain in preterm infants. We hypothesized that, compared to babies who received a human touch–based treatment, facilitated tucking, infants on Calmer would have lower behavioural and physiological pain indices during a single blood test required for clinical care. Methods: Forty-nine preterm infants, born between 27 and 36 weeks of gestational age, were randomized either to facilitated tucking or Calmer treatment. Differences between groups in changes across 4 procedure phases (baseline 1, baseline 2, poke, and recovery) were evaluated using (1) the Behavioral Indicators of Infant Pain scored by blind coders from bedside videotape and (2) heart rate and heart rate variability continuously recorded from a single-lead surface ECG (lead II) (Biopac, Canada) sampled at 1000 Hz using a specially adapted portable computer system and processed using Mindware. Results: No significant differences were found between groups on any outcome measures. Conclusion: Calmer provided similar treatment efficacy to a human touch–based treatment. More research is needed to determine effects of Calmer for stress reduction in preterm infants in the neonatal intensive care unit over longer periods.